Influenced CD cells and ICAM-1 by pulmonary surfactant combined with high-frequency oscillatory ventilation and its effects on immune function in children with neonatal respiratory distress syndrome - Su, Lijie; Sun, Qiuyu; Cai, Wenfang; Qi, Ying (Cellular and Molecular Biology, 2020)
This study aimed to explore the clinical efficacy of pulmonary surfactant combined with high-frequency oscillatory ventilation (HFOV) on neonatal respiratory distress syndrome (NRDS) and its influence on immune function in children. Children admitted to our hospital from March 2017 to March 2019 who received HFOV combined with pulmonary surfactant therapy as a research group. Sixty-two children received conventional nasal continuous positive pressure combined with pulmonary surfactant therapy as a control group. Clinical efficacy, blood gas and immune function of patients were compared between the two groups. The clinical efficacy of the research group was better than that of the control group (P< 0.050). PaO2 and PaO2/FiO2 were both higher after treatment (P< 0.050). CD3+ and NK cells in the research group were higher than those in the control group, while CD8+ cells and ICAM-1 were lower than those in the control group (P< 0.050). CD3+, CD4+ and NK cells decreased in both groups after treatment, while CD8+ cells and ICAM-1 increased (P< 0.050). HFOV combined with pulmonary surfactant has significant clinical efficacy and high safety on NRDS, and has a certain protective effect on children’s immune function. Hence, it is worthy of being the first choice for the clinical treatment of NRDS in the future.